Professionals’ digital competences and user profiles in social agencies and their impact on professional practice, family autonomy and wellbeing - Byrne, Sonia; Rodríguez, Guacimara; Álvarez, Míriam; Gutiérrez-Rodríguez, Nauzet; Rodrigo, María José; Padilla, Sonia; Martín, Juan Carlos (Frontiers in Psychology, 2024)
Introduction The health crisis of the last 3 years has revealed the weaknesses of the child and family support system based on the professional use of digital resources in social agencies. This study addresses three aims: to examine the level of professional digital competence; to analyze the user profiles in a variety of digital resources; and to test the impact of level of competences and user profiles on four aspects: professional practice, family satisfaction with the services, child and family wellbeing, and family autonomy in the exercise of the parenting role. Methods Participants were 148 practitioners from social agencies who voluntarily responded to an online survey with 47 questions. Results and discussion Results showed that professionals perceive themselves as more competent in areas of information / data management and communication / collaboration than in the creation of digital content, security measures, and technical problem solving. Websites, email, and instant messaging were the sources more frequently used and with higher satisfaction, than structured programs, social networks and multimedia content. Variability in the user profiles showed three clusters: Cluster 1 Social network user (n = 13), Cluster 2 Diversified user (n = 75) and Cluster 3 Communicative instant user (n = 60). Participants in Cluster 2 compared to those in the other clusters were the most proficient on their digital competences and acknowledge the positive impact of digital resources on their professional practice and the psychological and social wellbeing of families. This study points the need for improvement in professionals’ digital competences in some of the measured areas and the user profile of digital resources since both provide benefits on professional practice and family autonomy and wellbeing.